Characteristic patterns of mediation in developed countries - Ясиновський, Іван Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article examines the foreign experience in regulating mediation as one of the alternative methods of resolving legal disputes. Shows the reason for the selection of different models of mediation.